2018
DOI: 10.1177/0972622518792802
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Intention to the Use of Mobile Banking in Kerala: An Application of Extended Classical Technology Acceptance Model

Abstract: This research, using an extended version of classical technology acceptance model (TAM), investigates the factors influencing the adoption behaviour of mobile technology in banking. Survey data on 214 banking customers in Kerala were analysed under a structural equation modeling (SEM) framework and the results confirm the usefulness of TAM in predicting mobile banking adoption behaviour. The exogenous constructs from the original TAM, perceived usefulness (PU), and perceived ease of use (PEU) along with two ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Hypothesis 1: the result showed that perceived usefulness had a positive and significant relationship with the intention to use mobile banking, (p -value = 0.000 < 0 .05 and beta coefficient = 0.409). This was supported by previous researches of Mostafa and Eneizan(2018), andSaji and Paul (2018).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Hypothesis 1: the result showed that perceived usefulness had a positive and significant relationship with the intention to use mobile banking, (p -value = 0.000 < 0 .05 and beta coefficient = 0.409). This was supported by previous researches of Mostafa and Eneizan(2018), andSaji and Paul (2018).…”
supporting
confidence: 85%
“…As the literature reveals that different scholars employ different perspectives to assess the concern of security, risk, trust, and credibility, the concern has been conceptualized and assessed from a variety of ways that fully depends on which discipline researchers interpret the concern (Amin et al, 2012). Given that perceived credibility has b een empirically supported and used in mobile banking adoption studies (Al Khasawneh, 2015;Saji & Paul, 2018).…”
Section: P E R C E I V E D C R E D I B I L I T Ymentioning
confidence: 99%
“…Behavior intention is someone's subjective view of using fintech technology. In the ground theory, Technology acceptance model (TAM) explains that there is a positive influence between one's subjective views and one's intention to use fintech itself (Saji & Paul, 2018). This can explain if someone's subjective view of fintech is positive, which of course will produce a desire to use fintech in the future if they have the opportunity.…”
Section: Behaviour Intentionmentioning
confidence: 99%
“…Perceived costs are costs that someone will incur when adopting the technology. Costs that will be incurred by someone will be the main concern for someone to decide on the use of the technology (Saji & Paul, 2018). Can be said the number of additional costs that will be charged to the public or someone as a potential user to use fintech products and services will largely determine his decision…”
Section: Perceived Costmentioning
confidence: 99%
See 1 more Smart Citation